"Homo theologicus": toward a reflexive theology (with the help of Pierre Bourdieu) - Sanks, T. Howland (Theological studies, 2007)
The current conflictual situation of theology can be unterstood from a sociological perspective using the work of Pierre Bourdieu on the relationships of power in a given field. The article intends to help theologians be more reflexive about their task of interpreting the Christian symbol system.